Development of a Nomogram to Predict the Risk of Chronic Active Epstein-Barr Virus Infection Progressing to Hemophagocytic Lymphohistiocytosis - He, Xiaodan; Wang, Jingshi; Song, Deli; Wang, Zhao (Frontiers in Medicine, 2022)
Background: Chronic active Epstein-Barr virus infection (CAEBV) disease is sometimes associated with an aggressive clinical course, such as hemophagocytic lymphohistiocytosis (HLH). To explore the risk factors and predict the risk of CAEBV infection progressing to HLH, a retrospective research study was conducted. Methods: We retrospectively reviewed the medical records of 187 CAEBV-infected patients who were admitted to our center between January 2015 and December 2020. The patients were followed up until May 2021. The patients were divided into a progression-to-HLH group and a no-progression-to-HLH group. Demographic, clinical and laboratory data were collected for each patient. Results: Among the 121 CAEBV-infected patients who fulfilled the study’s inclusion criteria, 48 (30.7%) patients did not progress to HLH, and 73 (60.3%) patients progressed to HLH. The median time from CAEBV infection to progression to HLH was 14 months, and the number of patients who progressed to HLH within 1, 3, 5, and 10 years was 30 (24.8%), 56 (46.3%), 62 (51.2%), and 73 (60.3%), respectively. Multivariate analyses showed that the independent risk factors for CAEBV progression to HLH were plasma EBV-DNA load (OR=3.239, 95%CI 1.219–8.603, P=0.018), Platelet count (OR=0.991, 95%CI 0.985–0.998, P=0.010), elevated alanine aminotransferase (OR=1.019, 95%CI 1.005–1.034, P=0.009) and ≥2 of 3 lineages of cytopenia (OR=8.364, 95%CI 1.062–65.839, P=0.044). The regression coefficients (β) from the multivariate logistic model were used to construct a model for estimating the risk of CAEBV infection progressing to HLH. The discriminatory ability of the model was good, and the area under the receiver operating characteristic (ROC) curve (AUC) was 0.925. Conclusion: plasma EBV-DNA load, platelet count, elevated alanine aminotransferase and ≥ 2 of 3 lineages of cytopenia increase the risk of CAEBV infection progressing to HLH. A nomogram can be used to estimate the risk of CAEBV-infected patients progressing to HLH.